An association between pulmonary Mycobacterium avium-intracellulare complex infections and biomarkers of Th2-type inflammation - Paul E. Pfeffer; Susan Hopkins; Ian Cropley; David M. Lowe; Marc Lipman (Respiratory Research, 2017)
Abstract Background The rising incidence of pulmonary Mycobacterium avium-intracellulare complex (MAI) infection is unexplained but parallels the growing world-wide epidemic of allergic disease. We hypothesized an association between pulmonary MAI infection and Th2-type immune responses as seen in allergy. Methods Biomarkers of patient Th2-type immune responses (peripheral blood eosinophil counts and serum IgE levels) were compared between patients with positive pulmonary samples for tuberculosis and non-tuberculous mycobacterial (NTM) infection. A further comparison of clinical characteristics, including respiratory co-morbidities, and biomarkers, was conducted between patients culturing MAI NTM and those culturing NTM other than MAI. Results Patients culturing NTM from pulmonary samples had significantly higher peripheral blood eosinophil levels than those culturing Mycobacterium tuberculosis. Furthermore, patients culturing MAI compared to those culturing NTM other than MAI had higher eosinophil counts (mean 0.29x109/L vs 0.15x109/L, p = 0.010) and IgE levels (geometric mean 138kU/L vs 47kU/L, p = 0.021). However there was no significant difference in the frequency of asthma between the two NTM groups. Conclusions There is an association between biomarkers of Th2-type immune responses and pulmonary MAI. Prospective and translational research could identify the direction of causation; and so determine whether our finding may be utilized within future management strategies for MAI.